The Effect of Intravenous Essential Amino Acid Supplementation on Recovery of Kidney Function in Acute Kidney Injury Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia - Maya Sari; Novadian; Yulianto Kusnadi (HM Publisher, 2023)
Background: Acute kidney injury (AKI) is a clinical condition characterized by a rapid decline in kidney function that causes homeostatic failure in regulating fluid, electrolyte, and acid-base balance within hours to days. Nutritional supplementation is effective in replacing lost protein and as an energy reserve. This study aimed to determine the effect of intravenous essential amino acid supplementation on the recovery of kidney function in acute kidney injury patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia. Methods: This study is an open clinical trial of experimental research. A total of 34 research subjects participated in this study, where the subjects were grouped into treatment (IV amino acid supplementation) and placebo groups. Data analysis was carried out using STATA in univariate and bivariate. Results: Administration of amino acid supplements can reduce creatinine by 1.36. Meanwhile, the placebo was unable to reduce creatinine levels and even caused an increase in creatinine by 0.26. Conclusion: Intravenous administration of essential amino acid supplements has an effect on the recovery of kidney function in acute kidney injury patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia.